Assessment of physicochemical characteristics of groundwater within selected industrial areas in Ogun State, Nigeria. Issue 1 (1st January 2020) - Ojekunle, Zacchaeus Olusheyi; Adeyemi, Azeem Adedeji; Taiwo, Adewale Matthew; Ganiyu, Saheed Adekunle; Balogun, Mujeeb Adeyemi
ABSTRACT: This study aimed to assess the impacts of industrial activities in Ogun State, Nigeria. A total of 96 samples were collected both in dry and wet seasons for analysis of physicochemical quality indicators. Hydrochemical assessment were carried out according to APHA standard while hydrochemical facies of groundwater samples was evaluated using Piper Trilinear software. Pearson correlation was applied in order to determine the relationship between two parameters. The pH at Otta in wet season ranges from 6.67 ± 0.06 to 9.42 ± 0.11; dry season ranges from 4.35 ± 0.21 to 5.70 ± 0.14 while in Sagamu (wet season) values ranges from 6.01 ± 0.04 to 6.67 ± 0.06 while those of dry season ranged from 5.15 ± 0.07 to 6.55 ± 0.07. Interpretation of piper diagram revealed no specific dominant facie at Shagamu while most samples at Otta are characterized by the dominance of (Na+, K+) water types.